Promoting brain health in older adults through exercise: A narrative review of the role of muscle-brain crosstalk - Safoura Alizade; Mohammad Faramarzi (Journal of Exercise & Organ Cross Talk)
This article explores the impact of exercise training on brain health in older adults, focusing on the concept of muscle-brain crosstalk. As the global population ages, understanding how lifestyle interventions like exercise can support cognitive function is increasingly important. The article reviews evidence suggesting that physical activity, particularly aerobic and resistance training, plays a crucial role in maintaining and enhancing brain health. It discusses the mechanisms underlying the beneficial effects of exercise, including improved blood flow, neurogenesis, and the release of myokines proteins produced by muscle contractions that influence brain function. Additionally, the article highlights how these myokines facilitate communication between muscles and the brain, contributing to neuroplasticity, reduced inflammation, and enhanced cognitive abilities. The concept of muscle-brain crosstalk is emphasized as a key factor in understanding how exercise promotes brain health, with potential implications for designing targeted interventions to preserve cognitive function in older adults. The article concludes by suggesting that regular exercise should be a cornerstone of public health strategies aimed at improving the quality of life and cognitive health in aging populations. Further research is encouraged to deepen our understanding of the molecular pathways involved and to develop personalized exercise programs that maximize brain health benefits for older adults.